1998
DOI: 10.1029/98jc00783
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the southeast Indian Ocean from altimetry: Forcing mechanisms for the Leeuwin Current

Abstract: Abstract. Seasonal and interannual variability in the southeastern Indian Ocean is investigated with the aid of Topex/Poseidon (T/P) altimeter data for the 3-year period 1993-1995. The annual Rossby wave signal around 10øS is clearly marked, and consistent with modelling and Geosat results from earlier periods. A band of higher mesoscale variability between 20 ø and 35øS extends across the entire Indian Ocean, with characteristic timescales between 120 and 180 days and length scales of order 500 km. Sea level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 16 publications
5
54
1
Order By: Relevance
“…There may also be some remote influence from the Pacific, as suggested by Potemra [2001]. Rossby waves at (semi-)annual frequencies had already been identified in the southern Indian Ocean [Périgaud and Delecluse, 1992;Morrow and Birol, 1998]. Here we identify for the first time the strong four per year mode.…”
Section: Connection To the South Indian Oceanmentioning
confidence: 56%
“…There may also be some remote influence from the Pacific, as suggested by Potemra [2001]. Rossby waves at (semi-)annual frequencies had already been identified in the southern Indian Ocean [Périgaud and Delecluse, 1992;Morrow and Birol, 1998]. Here we identify for the first time the strong four per year mode.…”
Section: Connection To the South Indian Oceanmentioning
confidence: 56%
“…Seasonal variability of the LC creates strongest transport during the austral winter months, as opposing winds weaken (Godfrey and Ridgway, 1985;Feng et al, 2003). A peak in LC strength within the study area is observed from May to June each year, when the alongshore pressure gradient peaks (Morrow and Birol, 1998). While interannual peaks are driven by Pacific sea level variations, Ridgway and Godfrey (2015) have proposed a monsoonal sea level pulse as the driver of seasonal variations.…”
Section: Leeuwin Current In the Offshorementioning
confidence: 98%
“…The LC is unique as an eastern boundary current. Satellite observations show that this is the only eastern boundary region of enhanced mesoscale eddy activity (Schouten et al, 2005;Morrow and Birol, 1998). Across the SIO, the SICC flows against the direction of the wind (curl)-driven Sverdrup circulation that moves underneath it.…”
Section: Introductionmentioning
confidence: 99%